Management of skin adverse events associated with immune checkpoint inhibitors in patients with melanoma: A nursing perspective. Issue 5 (24th April 2017) - Thebeau, Melissa; Rubin, Krista; Hofmann, Matthias; Grimm, Julia; Weinstein, Alyona; Choi, Jennifer N.
Abstract: Purpose: Immune checkpoint inhibitors are associated with a unique immune‐related side effect profile that requires prompt recognition and management. Skin toxicities are the most common, and often earliest occurring, drug‐related adverse events (AEs) of any grade observed upon treatment with these agents. The purpose of this review is to provide practical guidance on the identification and treatment of skin AEs associated with the immune checkpoint inhibitors (ipilimumab, nivolumab, and pembrolizumab) from a nursing perspective, and demonstrate hands‐on application of the guidance using relevant patient case studies. Data sources: Data for drug‐related skin AEs were summarized from phase 3 nivolumab and nivolumab + ipilimumab trials and phase 2 and 3 pembrolizumab trials. Patient case studies were provided by the lead (M.T.) and senior (J.N.C.) authors. Conclusions: The recommendations presented here, based on accumulated clinical trial and clinical practice experience are consistent with established treatment guidelines and reach beyond established guidelines and recommendations for the management of AEs associated with immune checkpoint inhibitors. Implications for practice: The practical treatment guidance presented here may help familiarize medical teams with the recognition and management of skin AEs associated with these recently approved agents. The enclosed recommendations may contribute to optimized treatment through awareness of typical time to onset and clinical presentation, knowledge of management options, and appropriate application of treatment.